2020
DOI: 10.1111/jonm.12854
|View full text |Cite|
|
Sign up to set email alerts
|

Emergency medical staff’s perceptions on cultural value difference‐based teamwork issues: A phenomenological study in China

Abstract: Aim:To explore how different cultural values are connected to teamwork between doctors and nurses in emergency departments (EDs) in China.Background: China is a multicultural society, which leads to different cultural values being represented within its population. Doctors and nurses from different cultural backgrounds bring their own cultural values to their workplaces that influence teamwork. EDs are medical treatment facilities designed to provide episodic care to patients suffering from acute injuries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Three studies comparing the results between China and the US show higher scores on "teamwork within units" in Chinese hospitals but mixed results on "teamwork across units" and "communication openness" (29,37,42), proposing the value attached to the harmony in the Chinese culture as an explanation. Another Chinese cultural trait, collectivism, is reported to promote mutual support (43). These findings and inferences form first evidence on teamwork in China in relation to cultural differences with Western countries.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Three studies comparing the results between China and the US show higher scores on "teamwork within units" in Chinese hospitals but mixed results on "teamwork across units" and "communication openness" (29,37,42), proposing the value attached to the harmony in the Chinese culture as an explanation. Another Chinese cultural trait, collectivism, is reported to promote mutual support (43). These findings and inferences form first evidence on teamwork in China in relation to cultural differences with Western countries.…”
Section: Discussionmentioning
confidence: 60%
“…Staff younger than 30 years perceive better overall teamwork than those older than 30 years in one study (38) but score team cohesion significantly lower than those between 40 and 50 years old in another study (41). In addition, cultural values are considered to affect team processes (43). Feminine traits (e.g., friendship, enthusiasm, and patience) are shown to be beneficial to communication; collectivism facilitates the mutual support, while a clique culture hinders it.…”
Section: Relationship Between Inputs and Processesmentioning
confidence: 94%
See 1 more Smart Citation
“…A review of the raw data revealed this was due to the variation in the advocate item in the Strong Interpersonal Skills dimension. In Chinese culture, it appears that advocates are rarely associated with interpersonal communication skills in nursing [ 39 ]. The items in the Lack Authority/Professional Identity dimension, on the other hand, are more likely to be influenced by self-perception and society [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the majority of them have less/no staffing or management-relevant knowledge/experience, and the concept of workplace competition has not appeared to be instilled, 29 which prevents them from participating in the staffing/management of the NH. Besides, due to the general management culture in China, there exists strict leadership hierarchy between superiors and subordinates in which management layers tend to be exclusively in charge of such kind of staffing matters, 30 and most employees perceive themselves not being in the position to intervene with the upper management. The removal of 'non-punitive response to mistakes' and 'communication openness' may be related to the fact that the 'learn from error' climate and 'open communication' have not been well developed in domestic organisations.…”
Section: Open Accessmentioning
confidence: 99%